The Role of the Debt‐Service Ratio as a Leading Indicator of Households Consumption. (30th January 2019) - Apergis, Nicholas
Abstract : Given that household debt raises certain concerns about the resilience of the economy, against this backdrop, this paper explores whether household debt‐service matters as a leading indicator for consumption. Employing data from 32 countries, spanning the period 1999–2017 and the empirical analysis provides fresh information on the fact that the debt‐service ratio strongly predicts consumption expenditure. The results also document that the effect of the debt‐service ratio on consumer expenditure differs across types of consumer spending (durables vs nondurables vs services). In particular, the impact is strong for the case of the durable goods and weaker in the other two cases. The findings imply that debt‐service may serve as an important channel, running from debt to consumer spending. Finally, the results survive a number of robustness tests, while liquidity constraints seem to dominate the drivers of household consumption decisions.